Discovery and partial characterization of a non-LTR retrotransposon that may be associated with abdominal segment deformity disease (ASDD) in the whiteleg shrimp Penaeus (Litopenaeus) vannamei - Sakaew, Waraporn (BioMed Central, 2013)
BACKGROUND: Abdominal segment deformity disease (ASDD) of cultivated whiteleg shrimp Penaeus (Litopenaeus) vannamei causes economic loss of approximately 10% in affected specimens because of the unsightliness of distorted abdominal muscles. It is associated with the presence of viral-like particles seen by electron microscopy in the ventral nerve cords of affected shrimp. Thus, shotgun cloning was carried out to seek viral-like sequences in affected shrimp. RESULTS: A new retrovirus-like element of 5052 bp (named abdominal segment deformity element or ASDE) was compiled by shotgun cloning and 3′ and 5′ RACE using RNA and DNA extracted from ventral nerve cords of ASDD shrimp. ASDE contained 7 putative open reading frames (ORF). One ORF (called the PENS sub-domain), had a deduced amino acid (aa) sequence homologous to the GIY-YIG endonuclease domain of penelope-like retrotransposons while two others were homologous to the reverse transcriptase (RT) and RNaseH domains of the pol gene of non-long terminal repeat (non-LTR) retrotransposons (called the NLRS sub-domain). No single amplicon of 5 kb containing both these elements was obtained by PCR or RT-PCR from ASDD shrimp. Subsequent analysis indicated that PENS and NLRS were not contiguous and that NLRS was a host genetic element. In situ hybridization using a dioxygenin-labeled NLRS probe revealed that NLRS gave positive reactions in abdominal-ganglion neurons of ASDD shrimp but not normal shrimp. Preliminary analysis indicated that long-term use of female broodstock after eyestalk ablation in the hatchery increased the intensity of RT-PCR amplicons for NLRS and also the prevalence of ASDD in mysis 3 offspring of the broodstock. The deformities persist upon further cultivation until shrimp harvest but do not increase in prevalence and do not affect growth or survival. CONCLUSIONS: Our results suggested that NLRS is a shrimp genetic element associated with ASDD and that immediate preventative measures could include shorter-term use of broodstock after eyestalk ablation and/or discard of broodstock that give strong RT-PCR reactions for NLRS. In the longer term, it is recommended, if possible, that currently used, domesticated shrimp lines be selected for freedom from NLRS. The molecular tools developed in this work will facilitate the management and further study of ASDD.